Youth informality in Brazil: An analysis of school-to-work transitions - Romanello, Michele (2018)
This paper provides evidence that an individual’s educational attainment level is important in determining one’s participation the in labour market. These empirical results are obtained through an analysis of school-to-work transitions using competing risks regression. In this model, individuals transition from school into three different categories: formal job, informal job, or unemployed. This analysis draws data from the Monthly Employment Survey (PME) from January 2008 to December 2013. The findings from this paper suggest that educational attainment level is a significant factor in determining youths’ choice between pursuing formal and informal labor opportunities.